Institutional Framework for Human Rights Protection in Americas: The Inter-American Commission on Human Rights - Czepek, Jakub J. (Regional Human Rights Protection Systems Outside Europe, 2026)
The Inter-American Commission on Human Rights (IACmHR, Commission) was established by the Organization of American States (OAS) in 1959. Together with the Inter-American Court of Human Rights (IACtHR), formed by the American Convention on Human Rights (ACHR)1 in 1969, it provides the institutional framework for States’ Parties obligations with the ACHR. The Commission is a crucial element of the Convention and the only possibility to bring a case before the IACtHR leads through IACmHR. However, the Commission is not a typical regional human rights system responsible only for processing individual applications and forwarding it to the Court. It is a multipurpose organ, which has wide competence, focused especially on ‘observance and promotion of human rights’.2 The IACmHR is not established by the ACHR. It was created 10 years earlier, as an OAS organ.3 This enables the Commission to have a greater influence on human rights protection within the OAS framework. This chapter focuses solely on the Commission. It examines the Commission’s history and legal basis, scope of competence and procedure of individual petitions to the IACmHR. Keywords: Inter-American Commission on Human rights, IACmHR, ACHR, procedure, Inter-American human rights protection system